On Not Canonical Equivalence Between Diffeomorphism Subgroupoid And Fundemental Fibre Bundle (Journal of the College of Basic Education, 2022)
The main purpose of this work is to find not canonical equivalence to category and morphism of diffeomorphism from smooth manifold category with Fundemental Fibre Bundle denoted by groupoids morphism and denoted P.